2004
DOI: 10.1089/1092642041255397
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience with the Four-Arm Computer-Enhanced Telesurgery Device in Foregut Surgery

Abstract: The da Vinci robot with the addition of the fourth arm results in a efficient and safe operation and allows the surgeon to perform additional maneuvers without the use of a surgical assistant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…For this reason, minor misplacement of the trocars away from the ideal positions may severely hinder the performance of operations (24). The computer-assisted device must be positioned for maximum range of motion to its moving arms without collision of the arms or injury to the patient (38).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, minor misplacement of the trocars away from the ideal positions may severely hinder the performance of operations (24). The computer-assisted device must be positioned for maximum range of motion to its moving arms without collision of the arms or injury to the patient (38).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies had reported that RPEH is not associated with statistically significant increases in operative times when compared with RF [26]. It has been suggested that technically superior hiatal repairs can be achieved with RPEH, although in long-term follow-up comparisons to a laparoscopic PEH cohort this has not been shown [27,28].…”
Section: Foregut Surgerymentioning
confidence: 99%
“…The use of an additional fourth instrumentation arm has proven useful in anti-reflux surgery [19], potentially diminishing the need for a tableside assistant. Our results are compared with manual laparoscopic cholecystectomies, performed during the same period.…”
Section: Introductionmentioning
confidence: 99%